The influence of promotional costs on third party finds at PT. Bank BRI Syariah Indonesia - Hieronimus Erwin Indrawan; Suci Dwi Purwati; Amalia Tresna Fadhilah; Yudha Febri Al Paksi; Woro Dwi Hartanty (Institute of Computer Science (IOCS), 2023)
Banks receive a lot of funds from the public in the form of deposits, both in the form of Savings, Deposits, and other forms of savings offered by the Bank through the